2013
DOI: 10.4193/rhin12.090
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal surgery for skull base tumours: technique and preliminary results in a consecutive case series report

Abstract: patients (8%). One patient died 3 months after surgery due to a severe systemic sepsis. Conclusion:The extended endoscopic endonasal approach could be used as a minimally invasive and innovative technique for the removal of selected skull base lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 19 publications
1
26
0
8
Order By: Relevance
“…13 Macro-adenoma was noted in 67% of cases in our study, which is comparable to studies in which 70% of their cases were macroadenomas. 11,12 Visual function improvement was achieved in 82% of patients in this study, and this improvement was nearly the same as in other studies in which 90% of cases showed visual improvement after surgery. 12,13 In both studies, the majority of cases that developed better visual results complained of pituitary macroadenomas.…”
supporting
confidence: 89%
“…13 Macro-adenoma was noted in 67% of cases in our study, which is comparable to studies in which 70% of their cases were macroadenomas. 11,12 Visual function improvement was achieved in 82% of patients in this study, and this improvement was nearly the same as in other studies in which 90% of cases showed visual improvement after surgery. 12,13 In both studies, the majority of cases that developed better visual results complained of pituitary macroadenomas.…”
supporting
confidence: 89%
“…This pan-European survey provides further evidence of the high prevalence of musculoskeletal problems attributed to ESS among rhinologists. Endoscopic skull base procedures are longer and physically more demanding than standard ESS cases, and are becoming more common (28) . This will only serve to…”
Section: Resultsmentioning
confidence: 99%
“…This technique requires a team approach with an ENT and neurosurgeon who both must be experienced in endoscopic principles, skull base anatomy and have a vast understanding of all potential treatment options [1,2,[4][5][6]. An enormous learning curve exists not only for performing the surgical approach but also for dissection and removal of the lesion and subsequent reconstruction of the surgical defect and complication avoidance.…”
Section: Surgical Corridors and Types Of Lesion Approaches Treatable mentioning
confidence: 99%
“…They are typically related to either damage to major vascular structures or perforating vessels, optic nerve and chiasm or cranial nerves [1,2,[4][5][6][7][8]. New or worsening visual symptoms are rare and their occurrence varies considerably based on pathology.…”
Section: Complications Associated With Eeamentioning
confidence: 99%
See 1 more Smart Citation